Fold-thrust-belt structure of the Proterozoic Eastern Ghats Mobile Belt: A proposed correlation between India and Antarctica in Gondwana - BISWAL, TK; SINHA, S (Gondwana Research, 2004)
The Proterozoic Eastern Ghats Mobile Belt along the east coast of India shares a thrusted lower contact with the surrounding cratons. The thrust, known as the Terrane Boundary Shear Zone, is associated with two large lateral ramps resulting in a curved outline on the northwestern corner of the mobile belt. The Eastern Ghats Mobile Belt is divided into two lithotectonic units, the Lathore Group and the Turekela Group, based on their lithological assemblages and deformational history. On the basis of published data from a Deep Seismic Sounding (DSS) profile of the Eastern Ghats crust, the Terrane Boundary Shear Zone is considered to be listric in nature and acts as the sole thrust between craton and mobile belt. The Lathore and Turekela Groups are nappes. With this structural configuration the NW part is described as a fold thrust belt. However, the thrusting postdates folding and granulite metamorphism that occurred in the Eastern Ghats, as in the Caledonide type of fold thrust belt of NW Scotland. The Terrane Boundary Shear Zone is interpreted to be contiguous with the Rayner-Napier boundary of the Enderby Land in a Gondwana assembly.